Anterior Crossbite Correction with a Lower Removable Appliance. (2nd January 2019) - Borrie, Felicity; Bearn, David
Abstract : This case demonstrates the use of a novel design of lower removable appliance to correct an anterior crossbite, by retracting the lower incisors. CPD/Clinical Relevance: Patients usually do not tolerate lower removable appliances; however, this case highlights how a simple modification to a lower removable appliance can make it patient friendly and a useful appliance in the management of anterior crossbites in those cases where an upper appliance is not appropriate.